2005
DOI: 10.1163/156854105774355527
|View full text |Cite
|
Sign up to set email alerts
|

Increased penetration of host roots by nematodes after recovery from quiescence induced by root cap exudate

Abstract: Fourteen of 20 plant species surveyed produced root cap exudates that induced a state of reversible quiescence in Meloidogyne incognita and Caenorhabditis elegans. Exudate from six species failed to induce quiescence in either nematode species. Root cap exudates from pea were found to trigger quiescence in populations of plant-parasitic, animal-parasitic, insect-pathogenic, and free-living nematode species. One animal parasite was resistant. Caenorhabditis elegans strains with defects in known metabolic pathwa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 31 publications
(38 reference statements)
0
5
0
Order By: Relevance
“…For example, in vitro assays showed that Ditylenchus destructor was attracted to sweet potato crude root exudates (Xu et al, 2015). In addition, water-soluble metabolites exuded from the root tip of green pea (Pisum sativum L.) and maize resulted in a dormancy-like state in nematodes and reduced their infectability (Zhao et al, 2000;Hawes et al, 2005).…”
Section: Interactions With Phytophagous Nematodesmentioning
confidence: 99%
“…For example, in vitro assays showed that Ditylenchus destructor was attracted to sweet potato crude root exudates (Xu et al, 2015). In addition, water-soluble metabolites exuded from the root tip of green pea (Pisum sativum L.) and maize resulted in a dormancy-like state in nematodes and reduced their infectability (Zhao et al, 2000;Hawes et al, 2005).…”
Section: Interactions With Phytophagous Nematodesmentioning
confidence: 99%
“…For instance, root exudates of cucumber and their fractions having both repellent and attractant activity to M. incognita were reported (Castro et al 1989). Similarly, the root cap exudates that include enzymes, antibiotics, and other soluble chemicals and mucilage repelled both plant parasitic nematodes and free-living nematode Caenorhabditis elegans and resulted in reversible state of immobility in these nematodes (Hubbard et al 2005;Wuyts et al 2006;Zhao et al 2000). This study indicates that the root tip delivered products has the potential to temporarily immobilize nematodes.…”
Section: Plant-faunal Interactionsmentioning
confidence: 79%
“…Root exudates from several plant species also attract nematodes. Lauric acid from crown daisy ( Chrysanthemum coronarium L.) can be nematocidic when presented in certain concentrations, while the root cap exudates from several plant species can immobilize nematodes in a reversible fashion ( 13 , 36 ). This suggests that plant exudates are not only used by nematodes for host finding but also may be a mechanism to protect plants from pathogens or even capture prey.…”
Section: Discussionmentioning
confidence: 99%